2011
DOI: 10.1097/yic.0b013e32834309fc
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, double-blind, placebo-controlled study of sildenafil citrate in Canadian men with erectile dysfunction and untreated symptoms of depression, in the absence of major depressive disorder

Abstract: Depression and erectile dysfunction (ED) often co-occur. Phosphodiesterase type 5 inhibitors are effective in men with ED and untreated depression, or ED secondary to antidepressants. This study evaluated sildenafil treatment in Canadian men with clinically diagnosed ED (Sexual Health Inventory for Men score ≤ 21) and mild-to-moderate untreated depressive symptoms [Beck Depression Inventory II (BDI-II) score 14-28], but excluding major depressive disorder. Pretreatment screening using the Sexual Health Invento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The 40 included publications reported findings from 32 RCTs of PDE5 inhibitor treatment of men with ED. There were 28 single‐ or double‐blind, placebo‐controlled, parallel‐group trials [9,16,20–45], one treatment‐controlled, parallel group trial [46], and three open‐label trials [15,47,48]. In addition, there were five pooled analyses of RCT data [14,49–52] and three secondary or subgroup analyses of RCT data [53–55].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 40 included publications reported findings from 32 RCTs of PDE5 inhibitor treatment of men with ED. There were 28 single‐ or double‐blind, placebo‐controlled, parallel‐group trials [9,16,20–45], one treatment‐controlled, parallel group trial [46], and three open‐label trials [15,47,48]. In addition, there were five pooled analyses of RCT data [14,49–52] and three secondary or subgroup analyses of RCT data [53–55].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were conducted in men with clinically diagnosed ED who were in a stable relationship and who were treated with a PDE5 inhibitor for 6 to 12 weeks (Tables and ). Only three publications [30,31,43] did not report relationship stability as an eligibility criterion. All publications reported that men had ED for at least 6 months (where relevant), and most men had ED for at least 3 years (Tables and ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Men with severe depression have a twofold probability for ED compared to nondepressed subjects [57]. Depression as the consequence of ED was assessed in a recent Canadian study together with the effect of sildenafil citrate, PDE5-I, in patients with untreated depressive symptoms [58]. …”
Section: Ed In Elderly Men Affected With Psychiatric Disordersmentioning
confidence: 99%
“…Studies of men with erectile dysfunction and depressive symptoms (but not undergoing antidepressant treatment) also show that prescription of PDE-5 inhibitors is often accompanied by a reduction in depressive symptoms, enhanced quality of life, and improved interpersonal relationships [112][113][114] . Furthermore, preclinical studies suggest that nitric oxide activity is an important vulnerability factor in the Flinders rat depressive phenotype 115 , that passage of PDE-5 inhibitors across the blood-brain barrier can occur 116 , and that sildenafil has antidepressant-like effects after central muscarinic receptor blockade 117 .…”
Section: Management Of Treatment-induced Sexual Dysfunction In Depresmentioning
confidence: 99%